CONTRASTIVE ANALYSIS OF USING NOUN PHRASE IN ENGLISH AND INDONESIAN LANGUAGE - Soni Tantan Tandiana (LP2M-PMP Universitas Siliwangi, 2015)
The aim of this research is to find out the use of Noun Phrase (NP) in English and Indonesian language, and the similarity as well as the differences in constructing the elements used. This research was conducted based on the fact that the students in university level frequently make some interlingual errors that is the error done by adopting the grammatical pattern of mother tongue (L1) into the target language (L2) particularly in translating NP from English into Indonesian.Research method uses content analyses. Research data are analyzed by using contrastive analysis technique. The research data resource is taken from scientific text about medical science entitled ‘Coronary Heart Disease’ and the result of its translation.The result of the research shows that there are a lot of similarities of NP usage in English and Indonesian. Such as: NP is constructed by the same elements, those are: head, determiner, modifier and prepositional phrase. The pattern of NP with pre-modifier quantitative adjective has the same form. There is the similarity of NP using prepositional phrase whether it is placed as pre- prepositional phrase or as post- prepositional phrase. The differences, in English, NP is commonly expanded to the fore side of the head; on the other hand, in Indonesian language, it is expanded to the back side of the head.